2023
DOI: 10.1177/03635465231157377
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anterolateral Ligament Reconstruction or Lateral Extra-articular Tenodesis for Revision Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis of Comparative Clinical Studies

Abstract: Background: After its success in restoring rotational stability and reducing failure rates in primary anterior cruciate ligament reconstruction (ACLR), lateral extra-articular tenodesis (LET) or anterolateral ligament reconstruction (ALLR) has been endorsed for use in revision ACLR surgery, where failure rates are historically higher. Purpose: To perform a systematic review and meta-analysis on whether the addition of a LET or ALLR results in superior clinical outcomes and stability compared with isolated revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…There were no consistent differences between isolated procedures and combined procedures with regard to patientreported outcomes or return to sport. Boksh et al showed similar results with revision ACL reconstruction 26 . In a systematic review and meta-analysis with 10 studies and 793 patients, there were no differences in Lysholm and Tegner scores between either LET or ALL reconstruction and isolated revision ACL reconstruction.…”
Section: Acl Reconstructionmentioning
confidence: 73%
“…There were no consistent differences between isolated procedures and combined procedures with regard to patientreported outcomes or return to sport. Boksh et al showed similar results with revision ACL reconstruction 26 . In a systematic review and meta-analysis with 10 studies and 793 patients, there were no differences in Lysholm and Tegner scores between either LET or ALL reconstruction and isolated revision ACL reconstruction.…”
Section: Acl Reconstructionmentioning
confidence: 73%
“…The conclusion was that although ACL revision is often accompanied by a LET procedure, the results are conflicting, and there is a lack of high-level studies. Recently, Boksh et al [ 44 ] investigated the effect of an anterolateral supplemental procedure in revision ACL-R in a meta-analysis. They included 10 comparative studies with a total of 793 patients [ 26 , 31 , 42 , 45 51 ] and concluded that a lateral extra articular augmentation in ACL revision surgery could improve rotational stability, subjective IKDC scores, and reduce graft failure rate compared to isolated ACL revision.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent the associated ALL reconstruction presented lower failure rates of the meniscal repair. [1][2][3][4][5] In patients with chronic ACL tears, the combined ALL reconstructions lead to better functional outcomes and…”
Section: Video Transcriptmentioning
confidence: 99%
“…Patients who underwent the associated ALL reconstruction presented lower failure rates of the meniscal repair. 1-5…”
Section: Video Transcriptmentioning
confidence: 99%